Imaging atlas of human anatomy - Weir, Jamie (Mosby, 2003)
This definitive atlas views normal anatomy through the complete range of imaging modalities. The 3rd edition has been updated to reflect advances in imaging technology, particularly in terms of CT, MR and ultrasound imaging. In all, 200 new diagnostic images have been added, and in response to user feedback, 25 new line diagrams have been added to aid interpretation of certain key images. The book therefore now includes over 700 photographs of outstanding clarity, as well as 35 interpretative artworks